Random processes with convex coordinates on triangular graphs - J. N. Boyd; P. N. Raychowdhury (International Journal of Mathematics and Mathematical Sciences)
Probabilities for reaching specified destinations and expectation values for lengths for random walks on triangular arrays of points and edges are computed. Probabilities and expectation values are given as functions of the convex (barycentric) coordinates of the starting point.